Digital Advertising Content Training for Traditional Herbal Medicine SMEs - Ihtiari Prastyaningrum; Denny Hardyanto; Prabakti Endramawan; Defit Prastyo; Filipus Yubeleo Dari Pratama (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The existence of SMEs is currently expected to be able to boost the country's economy. The increasing number of SMEs can make a very good contribution to improving the country's economy. Along with current technological developments, SMEs are also required to be able to take advantage of the existence of information technology in every business activity carried out. Both production and distribution activities. This is so that the business they run can continue to survive and thrive amid fairly tight competition. One of the capabilities of using information technology that is currently mandatory for business actors is the ability to use digital marketing. Digital marketing is a digital marketing method that utilizes internet technology. One of the SMEs currently being developed is the Traditional Herbal SMEs in Joketro Village, Parang Magetan District. This digital marketing training for herbal medicine business players is intended so that joketro traditional herbal medicine can reach further markets. If the results of herbal medicine marketing are increasing, the income of herbal medicine business actors will also increase automatically. From the implementation of the training activities, the number of participants who can create good advertising content has also increased before and after the training